Teaching Games for Understanding (TGfU) Learning Model on Learning Motivation in Soccer Learning - Andrianto , Joan Rhoby (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Low student learning motivation and a variety of learning models are needed so that it is not monotonous. A learning approach is needed to develop subject matter in the context of learning playing technique skills so as to develop student understanding during play and students can apply it during the game. To examine the Teaching Games for Understanding (TGfu) learning model on learning motivation in soccer learning. This type of research is an experiment with a non-randomised control group and a pretest-posttest design. The sample in this study were students of the Physical Education study programme of STKIP PGRI Jombang class 2021, students of class 2021A as the experimental group, and students of class 2021B as the control group, each class totaling 21 students. The instrument used to determine student motivation is a motivation questionnaire. The data was analysed using the independent sample t test using SPSS 24. The results of the data analysis show learning motivation with a sig (2-tailed) of 0.000 <0.05, meaning that there is a difference in learning motivation between the experimental group and the control group. There is a significant effect of the Teaching Games for Understanding (TGfu) learning model on learning motivation in soccer learning. The sample in this study was small and needs to be developed in a real-world context. Future research needs to examine more educators to be able to intervene with a larger sample.